Analisis Diglosia Teks Ḥiwār Modern Standard Arabic karya E. Schulz - Nasikul Mustofa Efendi; Makhisoh, Iis (STAI Ali bin Abi Thalib Surabaya, 2023)
This research aims to describe an analysis about Diglossia or the difference between Classical Arabic (fuṣḥā) texts and the other dialect in the conversation material or hiwar contained in the MSA book by E. Schulz. This research takes the library research from the qualitative approach as its method. Modern Standard Arabic (MSA)- in current eras- is the literary standard and one of the six official languages of the United Nations. And most printed material by the Arab League—including most books, newspapers, magazines, official documents, and reading primers for small children—is written in Modern Standard Arabic. However, the exigencies of modernity have led to the adoption of numerous terms. Speakers of Modern Standard Arabic do not always observe the intricate rules of Classical Arabic grammar (fuṣḥā). Modern Standard Arabic principally differs from Classical Arabic in three areas: lexicon, stylistics, and certain innovations on the periphery that are not strictly regulated by the classical authorities. The results from this research are (1) The examples of Diglossia founded in the selection of vocabulary as well as from the writing system and the chosen vocabularies; (2) then on grammatical arrangements that deviate far from the standard Arabic grammar which may be due to influences from foreign languages that have been absorbed by some dialects. And (3) The third differences saw in phonology. The differences in the pronunciation of some letters are clearly heard in the audio of the conversation. The impact is that if a student does not know the difference phoneme system it will be difficult for him to identify the word and understand the meaning of the material in the book.